Effects of macrolide antibiotics on blood inflammatory mediators and organ damage markers in lipopolysaccharide-induced pulmonary damage rats - Ayşe Er; Enver Yazar (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine the effect of macrolide antibiotics using in veterinary area on serum/ plasma inflammatory mediators and organ damage markers in lipopolysaccharide-induced pulmonary damage rats. Materials and Methods: Total 198 Sprague-Dawley rats were used. Six rats were used for a 0th sampling point for all groups. 192 rats were divided into four equal groups as lipopolysaccharide (Escherichia coli 0111:B4, 0.5 mg/200 μl, intratracheal), lipopolysaccharide + tylosin (10 mg/kg, subcutaneously), lipopolysaccharide + tilmicosin (20 mg/ kg, subcutaneously) and lipopolysaccharide + tulathromycin (2.5 mg/kg, subcutaneously). After the treatments, blood samples were collected by cardiac puncture under anesthesia at 0.5, 1, 1.5, 2, 4, 6, 12 and 24 hours. Serum tumor necrosis factor α, interleukin-1β, interleukin-6, interleukin- 10 levels, and plasma 13, 14-dihydro-15-ketoprostaglandin F2α levels were determined by ELISA, while serum C-reactive protein, creatine kinase-MB, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, cholesterol, triglyceride, blood urea nitrogen and creatinine levels were determined by otoanalyzer. Area under the concentration time curve (AUC0-24), maximal concentration in plasma or serum (Cmax) and time to reach Cmax (tmax) values were determined by pharmacokinetic computer program. Results: Macrolide antibiotics increased serum tumor necrosis factor α and plasma 13, 14-dihydro-15-keto-prostaglandin F2α levels. Conclusion: Macrolide antibiotics used in veterinary area may no shown depression on immune system. Hovewer, investigation is need that especially dose-depended manner effects of macrolide antibiotics on immunosystem.